The Impact of Online Services on Developing Students’ Media Competence - Simonova, Irina; Ustiugova, Tatiana; Yakovleva, Olga (International Journal of Research in E-learning, 2017)
In this article, the authors describe their experience of introducing students to online services for developing electronic educational resources with multimedia content. The sample of research included pedagogical education students from different years of first degree (bachelor) studies. The article presents the results obtained in the Herzen State Pedagogical University of Russia. The authors developed an e-environment for a training module, with all the content and interaction algorithms. In the experiment, the authors measured various indicators of students’ media competence development: informational, perceptual, motivational, contact, and interpretation (based on A. V. Fedorov’s approach). After students had studied the proposed module, the analyses of their projects were made.